Review of the Legal Policy on MSME Debt Cancellation based on Economic Analysis of Law - AILSA AILSA NOVELITA; Laga Sugiarto (Law Research Review Quarterly, 2025)
This research aims to analyze and review the policy of eliminating MSME debt in Indonesia based on Government Regulation Number 47 of 2024. As a government commitment to support the sustainability of MSME businesses that experience financial constraints due to bad loans. The approach is carried out using normative juridics with the specifications of applicable laws and regulations, study of documents and literature. The results of the study show that this policy depends on clear implementation, alignment in legal regulations, clear mechanisms, and supervision from the government or financial institutions. The realization of this policy needs to be optimized to support the clearer, more effective, and transparent elimination of MSME debt